The Influence of Electronic Word of Mouth (E-WOM) and Brand Image on Consumer Loyalty with Consumer Satisfaction as a Mediating Variable on Samsung Smartphone Users in Banten Province - Khadafi, Daffa Muhammad; Ramdansyah, Agus David; Setya, Yanto Azie (Management Science Research Journal, 2025)
The purpose of this study was to examine the effect of electronic word of mouth (E-WOM) and brand image on consumer loyalty with consumer satisfaction as a mediating variable on Samsung smartphone users in Banten Province. Data analysis was conducted on 180 respondents using regression with smartPLS software version 4.1.1.2 which was used to test the seven hypotheses in this study. The results of this study indicate that: (1) electronic word of mouth (E-WOM) has a negative and insignificant effect on consumer loyalty. (2) brand image has a positive and significant effect on consumer loyalty. (3) electronic word of mouth (E-WOM) has a positive but insignificant effect on consumer satisfaction. (4) brand image has a positive and significant effect on consumer satisfaction. (5) consumer satisfaction has a positive and significant effect on consumer loyalty. (6) consumer satisfaction is unable to mediate the effect of electronic word of mouth (E-WOM) on consumer loyalty. (7) consumer satisfaction is able to partially mediate the effect of brand image on consumer loyalty